A retrospective study of anesthesia during rigid bronchoscopy for airway foreign body removal in children: propofol and sevoflurane with spontaneous ventilation. Issue 10 (22nd August 2014) - Chai, Jun; Wu, Xiu‐Ying; Han, Ning; Wang, Li‐Yin; Chen, Wei‐Min; Cote, Charles
Summary Background Tracheobronchial foreign body aspiration is a significant cause of childhood morbidity and mortality. We analyzed our experience in management of aspirated foreign bodies, including methods of anesthesia used, over a 4‐year period. Methods We retrospectively reviewed the records of tracheobronchial foreign body removal by rigid bronchoscopy with spontaneous ventilation in 435 children. All patients had received initial anesthesia with inhaled sevoflurane. One hundred and ninety‐seven patients (Group PropRemi) then received intravenous propofol and remifentanyl for maintenance of anesthesia; the remaining 238 patients (Group PropSevo) received propofol and sevoflurane. Results Tracheobronchial foreign body was found in 405 children (93.1%) and successfully removed from 402 (99.3%) children. Among three patients who failed bronchoscopy, one child suffered cardiac arrest and died during the bronchoscopy, and two required subsequent tracheotomy for foreign body removal. Adverse effects (intraoperative coughing, breath holding, body movement, bronchospasm, and laryngospasm) were significantly more frequent in Group PropRemi than in Group PropSevo. No complications such as bleeding, pneumothorax, pneumomediastinum, or the need for thoracotomy were encountered. Conclusion Sevoflurane induction followed by a combination of sevoflurane and continuous infusion of propofol resulted in fewer adverse events than sevoflurane induction followed by TIVA with propofol and remifentanyl during rigid bronchoscopy for airway foreign body removal in children with spontaneous ventilation.